2021
DOI: 10.1108/ijge-03-2021-0052
|View full text |Cite
|
Sign up to set email alerts
|

Female entrepreneurship in emerging markets: challenges of running a business in turbulent contexts and times

Abstract: PurposeThe present study seeks to investigate female entrepreneurship in turbulent times (COVID-19) and contexts (emerging markets).Design/methodology/approachAn in-depth, multiple-firm (five SMEs), cross-country (2 countries – Brazil and Tunisia), cross-region (Latin America and the MENA region) case study based on a mixed embeddedness perspective.FindingsThe study highlights how challenges and uncertainties are managed, what inspires female entrepreneurs and what frightens them. We capture these entrepreneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 55 publications
1
23
0
1
Order By: Relevance
“…, 2018). In the context of Covid-19, interviews with Tunisian businesswomen garnered evidence that self-efficacy, resilience, and support networks have also proved important for female business owners in MENA countries (Kogut and Mejri, 2021). Studies focusing on the Gulf countries found that the main reasons to engage in entrepreneurship are a desire to be independent through additional income (Dechant and Al Lamky, 2005; Ghouse et al ., 2019, 2021) as well as self-fulfillment and a desire to contribute to their society (Itani et al.…”
Section: Female Entrepreneurs In the Mena Regionmentioning
confidence: 99%
“…, 2018). In the context of Covid-19, interviews with Tunisian businesswomen garnered evidence that self-efficacy, resilience, and support networks have also proved important for female business owners in MENA countries (Kogut and Mejri, 2021). Studies focusing on the Gulf countries found that the main reasons to engage in entrepreneurship are a desire to be independent through additional income (Dechant and Al Lamky, 2005; Ghouse et al ., 2019, 2021) as well as self-fulfillment and a desire to contribute to their society (Itani et al.…”
Section: Female Entrepreneurs In the Mena Regionmentioning
confidence: 99%
“…In pursuing both business opportunities and maintaining their maternal identity, it is undeniable that family dynamics may influence mumpreneurs. Especially after marriage, mumpreneurs are struggling to achieve a balance between business and family duties (Afshan et al, 2021; Kogut & Mejri, 2022; Panda, 2018). In some cases, mumpreneurs have to sacrifice the expansion of their businesses for fear of impeding their parenting responsibilities (Duberley & Carrigan, 2013; Ogundana et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Należy jednak odnotować, że powstały już opracowania niezwykle wartościowe, odnoszące się do tematyki szeroko rozumianej przedsiębiorczości indywidulanej (Piekutowska, 2021), również w kontekście wywieranego na nią ekonomicznego wpływu epidemii (Pietrasieński, 2021) oraz przedsiębiorczości kobiet w perspektywie prowadzenia biznesu w niespokojnych i kryzysowych czasach pandemii COVID-19, m.in. na rynkach wschodzących, w Irlandii, w Egipcie czy w Rosji (Kogut, Mejri, 2022;Stephens, 2021;Salman, 2021, Burowa, 2021, z wykorzystaniem finansowania społecznościowego (Alva, 2021), w perspektywie wpływu koronakryzysu na przeżywalność założonych firm (Hyland, 2021;Amandla, Beharry -Ramraj, 2022). Jednocześnie jest niemal pewne, że w najbliższych latach nie zabraknie tematów dotyczących wpływu pandemii koronawirusa na różne aspekty ludzkiego życia.…”
Section: Podsumowanie I Omówienie Wynikówunclassified